2014
DOI: 10.1111/jcap.12077
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Coping, and Sleep in Children and Adolescents With Sickle Cell Disease

Abstract: Children with SCD experience pain that affects sleep patterns and the way they cope with pain. Nurses need to concurrently assess pain, coping, and sleep and promote sleep hygiene and positive coping strategies during pain episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 55 publications
3
73
1
7
Order By: Relevance
“…Two-thirds of the participants reported experiencing pain in the preceding month, 91.2% had some degree of sleep disturbance, while 18.2% required sleeping medications. In this study, there was a non-statistically significant trend towards higher PSQI score with increasing pain severity, but not with pain frequency [193]. Two other studies showed that SCD was associated with increased frequency and severity of sleep disturbances in middle-school children and adolescents that resembled the patterns reported for other chronic pain syndromes (e.g., juvenile idiopathic arthritic and headache), with one notable exception e SCD was associated with a much higher prevalence of sleep-disordered breathing [194,195].…”
Section: Erectile Dysfunctioncontrasting
confidence: 62%
“…Two-thirds of the participants reported experiencing pain in the preceding month, 91.2% had some degree of sleep disturbance, while 18.2% required sleeping medications. In this study, there was a non-statistically significant trend towards higher PSQI score with increasing pain severity, but not with pain frequency [193]. Two other studies showed that SCD was associated with increased frequency and severity of sleep disturbances in middle-school children and adolescents that resembled the patterns reported for other chronic pain syndromes (e.g., juvenile idiopathic arthritic and headache), with one notable exception e SCD was associated with a much higher prevalence of sleep-disordered breathing [194,195].…”
Section: Erectile Dysfunctioncontrasting
confidence: 62%
“…50 In a cohort of children and adolescent SCD patients, depression was also associated with worse HRQoL scores in all domains. 51 Depression was found to be associated with neurocognitive deficits in other patient populations. 52,53 However, assessment of neurocognitive functions showed no difference between those with depression and those without depression in this study, perhaps because this population in general has altered neurocognitive functioning due to SCD-associated neurological complications.…”
Section: Discussionmentioning
confidence: 99%
“…On average, individuals with SCD report pain on 22% of days [41] and those with a diagnosis of avascular necrosis (AVN) experience more subjective sleep difficulties than those with SCD but no radiological evidence of AVN [80]. Studies of sleep disturbance in pediatric SCD have included both subjective [41,[80][81][82][83][84][85][86][87][88][89] and objective [85,[90][91][92][93] sleep measures; however, studies frequently lack a healthy control group and child self-report.…”
Section: Sickle Cell Diseasementioning
confidence: 99%